(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2018)
The rapid emergence of houses in the low-lying areas of developing countries, especially in South Asia, has led to increasing negative environmental effects in these regions. Therefore, here, an attempt is made to build a geo-spatial model that can be used as a guide and index to help understand how the unending emergence of individual households generally occurs. This study was conducted in the Colombo Metropolitan Region, in which the mass conversion of low-lying areas has already taken place to a great extent. The study was based on variables related to the behaviour of householders who were living in lowlying areas without having the proper legal right to occupy or use those lands. A spatial logistic model was developed based on seven explanatory variables, and this was used in conjunction with GIS-linked display maps to measure how the householders’ behaviour increased the level of conversion of low-lying lands. The sample size was 294 houses comprising 185 stable and 109 non-stable houses in the core study area, which formed a part of the Colombo Metropolitan Region. The results of this study show that out of the seven variables tested, five variables are highly significant, and the accuracy of the database is approximately 86.7%. A predicted probability map of the converted and nonconverted houses in the year 2012 has been categorised as an index of conversion. The final output of this study can be used as a guide and index with which to monitor, manage and shape low-lying areas during the town planning, house upgrading and rehabilitation stages.